Racismo institucional e relações de trabalho no Brasil - Santos, Júlio Cesar Silva (2021)
This thesis deals with the milestones that institutional racism establishes at work, and which public policies and affirmative actions can be implemented in favor of racial equality. The research problem lies in the indispensability of investigating how the articulation between institutional racism in labor relations undermines the implementation of racial diversity policies in the labor field. Regarding the conclusions and results achieved, the importance of changing protocols in public and private companies is highlighted, aiming at racial diversity policies, greater education of managers, adequacy of recruitment and selection areas, demonstrating the importance of racial diversity, and training for all employees of the institution, explaining the need for structural change in labor relations, aiming for a diverse environment with equal opportunities. In this way, it was concluded that the fight against structural racism and the superiority of whiteness in companies requires public policies and the construction of an anti-racist network that identifies racial exclusions.